Dynamics of 1.55 μm Wavelength Single-Mode Vertical-Cavity Surface-Emitting Laser Output under External Optical Injection. (14th November 2012) - Kim, Kyong Hon; Lee, Seoung Hun; Deshmukh, Vijay Manohar
Abstract : We review the temporal dynamics of the laser output spectrum and polarization state of 1.55  μ m wavelength single-mode (SM) vertical-cavity surface-emitting lasers (VCSELs) induced by external optical beam injection. Injection of an external continuous-wave laser beam to a gain-switched SM VCSEL near the resonance wavelength corresponding to its main polarization-mode output was critical for improvement of its laser pulse generation characteristics, such as pulse timing-jitter reduction, linewidth narrowing, pulse amplitude enhancement, and pulse width shortening. Pulse injection of pulse width shorter than the cavity photon lifetime into the SM VCSEL in the orthogonal polarization direction with respect to its main polarization mode caused temporal delay of the polarization recovery after polarization switching (PS), and its delay was found to be the minimum at an optimized bias current. Polarization-mode bistability was observed even in the laser output of an SM VCSEL of a standard circularly cylindrical shape and used for all-optical flip-flop operations with set and reset injection pulses of very low pulse energy of order of the 3.5 ~ 4.5 fJ.